ProGenomes3: approaching one million accurately and consistently annotated high-quality prokaryotic genomes. Issue Volume 51:Issue D1(2023) (21st November 2022) - Fullam, Anthony; Letunic, Ivica; Schmidt, Thomas S B; Ducarmon, Quinten R; Karcher, Nicolai; Khedkar, Supriya; Kuhn, Michael; Larralde, Martin; Maistrenko, Oleksandr M; Malfertheiner, Lukas; Milanese, Alessio; Rodrigues, Joao Frederico Matias; et al.
Abstract: The interpretation of genomic, transcriptomic and other microbial 'omics data is highly dependent on the availability of well-annotated genomes. As the number of publicly available microbial genomes continues to increase exponentially, the need for quality control and consistent annotation is becoming critical. We present proGenomes3, a database of 907 388 high-quality genomes containing 4 billion genes that passed stringent criteria and have been consistently annotated using multiple functional and taxonomic databases including mobile genetic elements and biosynthetic gene clusters. proGenomes3 encompasses 41 171 species-level clusters, defined based on universal single copy marker genes, for which pan-genomes and contextual habitat annotations are provided. The database is available at http://progenomes.embl.de/